Parent carer and disabled young people’s perspectives on the impacts of changes to service provision for children and young people in England during the COVID-19 pandemic: a qualitative study - Lindsay Pennington; Catherine Exley; Dawn Teare; Jeremy R Parr; Christopher Morris; Shona Haining; Ge Yu; Amanda Allard; Philip Heslop; Sara Carr; Hannah Merrick; Helen Driver; et al. (BMJ Open)
Objectives In England, the delivery of health, education and social care services changed substantially during COVID-19. Some services closed, some had reduced capacity and there was a shift to the use of telehealth. This study aimed to understand how families of children and young people with neurodisability experienced these service changes, what did or did not work well for them and what impact the service changes had on them.Design Qualitative study with parent carers of children (aged 0–19 years) with neurodisability accessing children’s health, social care and education-based services during the COVID-19 pandemic.Setting Participants were recruited from five local authority areas in England and interviewed via telephone and/or video call.Participants 48 parent carers (45 mothers, three fathers) were interviewed and nine young people (aged 8–16 years). Across the parent carers there were 55 children with neurodisability (43 males, 12 females), ranging from 3 to 19 years. Children had a range of diagnoses, including autism, attention deficit hyperactivity disorder, cerebral palsy, genetic conditions and epilepsy. Nine young people (aged 8–16 years; eight males, one female) were interviewed; two individually, three in a focus group and four with their parent carer.Results Four themes were identified: (1) communication of service changes, (2) access to services during the pandemic, (3) impacts of service changes and (4) learning for future emergencies and resetting services. Communication of service changes was reported as poor and confusing. Access to services during the pandemic varied. Medical services continued with least disruption; therapeutic, education-based and social care services were severely disrupted. Service changes had a detrimental impact on families coping with high levels of medical care and physical and behavioural support. Young people experienced negative impacts of service change on their physical, mental and behavioural health.Conclusions Services for children with neurodisability require a person-led, family centred approach with strong multidisciplinary team working. Findings indicated the need for improved communication within and between services, and between services and families and young people. Planning for future emergencies needs to factor in the specific health and care needs of children with neurodisability and maintain access to services, in particular, those accessed through schools.